Pengaruh Promosi Jabatan dan Tunjangan Kinerja Terhadap Produktivitas Kerja Pejabat Pengawas Pada Sekretariat Daerah Kabupaten Mamuju - Halim, Agus; Satria, Satria (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Measurement of work performance is carried out by calculating the value of performance achievement with productivity which is one component that must be owned by a Regional Secretariat of Mamuju Regency if it wants to achieve the goals set by the organization. The method used is the Quantitative Method by distributing questionnaires. The sample used in this study, the sample used was 59 employees with the rank of echelon IV. Sampling technique using saturated sampling, in this study all populations were sampled with a total of 59 respondents. Data processing technique by testing the research instrument using validity test, reliability test and multiple linear regression analysis, as well as t test (partial) and f test (simultaneous). Based on the data analysis that has been carried out in this study, the following conclusions were drawn: 1) Position promotion has a significant effect on the work productivity of supervisory officials at the Regional Secretariat of Mamuju Regency with a probability value of 0.009 <0.05 and a t value of 8.322 > t table value of 1.67303 , so the hypothesis is accepted. Performance allowances have a significant effect on the work productivity of supervisory officials at the Regional Secretariat of Mamuju Regency with a probability value of 0.001 <0.05, and a tcount value of 10,512 > a ttable value of 1,67303, the hypothesis is accepted. 2) The most dominant performance allowance has an effect on the work productivity of supervisory officials at the Regional Secretariat of Mamuju Regency with a beta coefficient value of 0.959 which is higher than the promotion of 0.646.